Analysis of the Efficiency and Effectiveness of Regional Spending in Improving the Quality of Public Services in the Medan City Regional Government for the 2023-2024 Fiscal Year - Marlina Marlina; Suci Azzahra; Vina Arnita (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
This study analyzes the efficiency and effectiveness of regional government expenditure in improving the quality of public services in the Government of Medan City for the 2023–2024 fiscal years. The objectives of this study are: (1) to measure the level of efficiency in the use of regional budgets for the provision of public services, (2) to assess the effectiveness of expenditure realization in achieving public service performance indicators, and (3) to provide policy recommendations to improve budget management performance. Quantitative analysis is conducted through document analysis of the Regional Revenue and Expenditure Budget (APBD) and expenditure realization for 2023–2024, calculation of efficiency ratios (comparison between budget inputs and service output indicators), and effectiveness analysis based on the achievement of Public Service Performance Indicators (PSPI) and regional performance targets. Qualitative analysis complements the quantitative findings through structured interviews with budget management officials and service users, as well as case studies of several strategic agencies, including health, education, licensing, and infrastructure sectors. The results indicate that, in aggregate, Medan City’s regional expenditure during the 2023–2024 period demonstrates a moderate level of efficiency. Certain sectors, such as health and education, are relatively efficient in converting budget allocations into service outputs, while infrastructure and licensing sectors still exhibit inefficiencies or unfocused expenditure realization. In terms of effectiveness, improvements in public service quality are observed in key indicators—such as administrative service completion time and user satisfaction—although achievements are uneven across agencies. The main contributing factors include insufficient outcome-based budget prioritization, limitations in human resource capacity, and suboptimal monitoring and evaluation systems. The study recommends strengthening outcome-based budget prioritization, enhancing planning and oversight capacity, implementing more measurable performance indicators, and leveraging service digitalization to improve operational efficiency. The implementation of these recommendations is expected to improve expenditure efficiency and effectiveness ratios and enhance the quality of public services in future periods.